In Defense of Robin Barrow's Concern About Empirical Research in Education - Martin, Jack (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2019)
This paper offers a defense of Robin Barrow’s main arguments in Giving Teaching Back to Teachers, including additional material concerning the inability of the aggregate data and statistical methods employed in research in education (and research on teaching) to speak to individual teachers and students or to particular classrooms. This defense and extension of Barrow’s position is applied in a critique ofa proposal made by Lorraine Foreman-Peck in her 2004 debate with Barrow, entitled What Use is Educational Research?, published in 2005 by the Philosophy of Education Society of Great Britain. A central confusion that attends and limits much empirical research in education and social science concerns conflation of two different senses of the concept general, as “common to all” or “on average.” The havoc this confusion plays ought not be ignored or minimized by educational researchers and their advocates who tend to exaggerate the empirical regularity in social scientific data and therefore the generalizability of social science research in education and elsewhere.